The Influence of Affiliate Marketing and Product Quality on Purchase Interest in Generation Z Tiktok Users in Medan - Amanda Damayanti Nasution; Nuri Aslami; Muhammad Ikhsan Harahap (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In Medan, Generation Z TikTok users are the target audience for this study, which seeks to determine the relationship between Affiliate Marketing and Product Quality. Here, the entire population is represented using quota sampling. The distribution of the Google Form questionnaire was used in collecting data for this study. On a Likert scale from 1 to 5, users of the TikTok Shop app responded, and the results were used to make statements about Affiliate Marketing, Product Quality, and Purchase Interest of Generation Z. Study of 100 people in Medan who rated themselves to be part of the “generation” the TikTok Shop app is done. The results of this study indicate that the influence of Affiliate Marketing on the customer’s tendency to buy increases significantly. The product Quality Variable has no positive or statistically significant effect on consumer interest in making purchases among TikTok application users in Medan who are members of Generation Z.